Treatment of COPD with a particular focus on biological therapy: a systematic review - Kinga Ziojła; Agnieszka Kuzio; Aleksandra Cieplińska (Nicolaus Copernicus University in Toruń, 2024)
Incroduction and aim. COPD is a heterogeneous condition characterized by persistent respiratory symptoms. These symptoms can significantly reduce the quality of life for patients. The conventional treatment used so far is not always effective, especially in cases of severe disease and in specific phenotypes, which is why researchers are constantly searching for new drugs. The aim of this paper is to review the published literature on the treatment of COPD, with particular emphasis on the role of biological therapy. Material and methods. Online databases were used for literature research. The review primarily included literature published after 2016. Analysis of the literature. Conventional pharmacological treatment for COPD patients mainly relies on the use of bronchodilators. Recently, researchers have increasingly focused on the potential use of biological therapy in COPD. The greatest hope lies in the broader use of biological therapy in patients with COPD with elevated eosinophil counts. One of the targets is the IL-33/ST2 pathway, which partially directs inflammatory and remodeling processes in COPD. Drugs belonging to this group include tozorakimab, itepekimab, and astegolimab. Another mechanism of action for biological drugs is blocking IL-5; drugs that work through this mechanism include mepolizumab and benralizumab. Dupilumab is a monoclonal antibody that, due to promising research results, currently has the greatest potential for expanding indications for the treatment of COPD. Conclusion. Since biological therapy offers hope for better disease control in specific groups of patients, further clinical research is necessary to explore the use of biological treatment. This could improve the quality of life for individuals with COPD, especially those who respond poorly to conventional treatment. Key words. COPD, chronic obstructive pulmonary disease, biology treatment